Research progress of novel anti-tumor drug formulations - Liu, Yan; Guo, Qie; Shi, YunYan; Cui, MengNa; Jing, FanBo (Frontiers in Oncology, 2024)
Cancers have become the second leading cause of death worldwide, following cardiovascular diseases.Traditional anti- cancer strategies, including radiotherapy chemotherapy, surgery, and targeted therapies, have been widely used but are often reassessed due to their significant side effects and relatively low cure rate. Recently, the development of novel formulations for anti-tumor drugs has gained considerable attention, marking a pivotal step forward in cancer treatment advancements. These innovative formulations aim to enhance the therapeutic efficacy of anti-tumor drugs by employing advanced drug formulation technologies and delivery systems. In particular, nano-drug delivery systems (NDDS) have emerged as a promising approach to improve drug targeting, reduce side effects, and overcome drug resistance. This review highlights recent progress in NDDS for anti-tumor drug development and explores the future prospects of these advanced formulations in improving cancer treatment outcomes.